"دراسة التحليلة لفجوة التوقعات للمراجعة الخاريجية للحسابات بالجزائر دراسة ميدانية ( عينة من محافظي الحسابات وخبراء محاسبين لدى ولاية الوادي)" - أحمد, شيحاني; عبد السلام, حابي; عبد الستار, محمد طاهر; مروان, باي (University of eloued جامعة الوادي, 2022)
" تهدف هذه الدراسة إلى رصد وتحليل مكونات فجوة التوقعات للمراجعة الخارجية للحسابات، والتي تعتبر مشكلة معاصرة عامة لا يمكن استثناء أي بيئة مراجعة منها، وهذا إسقاطا على بيئة الممارسة المهنية للمراجعة الخارجية للحسابات في الجزائر، من خلال الوقوف على مهام ومسؤوليات المراجع الخارجي للحسابات في الجزائر، من وجهة نظر المراجعين الخارجيين، وما ينتظره منهم المجتمع المالي من جميع الفئات المستفيدة من خدمات المراجعة الخارجية، والتي تتمثل في المهام والمسؤوليات والخدمات المنتظرة من المراجعين في ظل ما يحكم مهنة المراجعة من تشريعات وطنية، وتوافقا مع المعايير الدولية للمراجعة وهذا لغياب كلي لمعايير وطنية للمراجعة، مما يتيح لنا رصد فجوة التوقعات للمراجعة الخارجية للحسابات بالجزائر وتحليل مكوناتها أجريت الدراسة بالاعتماد على أسلوبين متكاملين الأول وثائقي (وصفي) بالاطلاع على عدد من الأدبيات لتوضيح الخلفية النظرية للتحفيزات الجبائية والاستثمار الفلاحي، أما الأسلوب الثاني مسحي (تحليلي) عن طريق دراسة استكشافية من خلال الاستبيان كأداة لجمع البيانات، إذ تم قياس معامل الصدق حيث أنه تم التوصل إلى درجة عالية من الثبات لعينة مكونة من (40) فردا تم تحليل البيانات باستخدام الحزمة الإحصائية (SPSS.V22) وأدوات إحصائية وصفية موجه إلى الخبراء المحاسبيين، محافظي الحسابات. ""This study aims to monitor and analyze the components of the expectations gap for external audit, which is considered a general contemporary problem from which no audit environment can be excluded, and this is a projection on the environment of professional practice of external audit in Algeria, by standing on the tasks and responsibilities of the external auditor in Algeria, From the point of view of the external auditors, and what the financial community expects of them from all groups benefiting from external audit services, which are represented in the tasks, responsibilities and services expected from the auditors in light of the national legislation governing the audit profession, and in line with international auditing standards, and this is due to the total absence of national standards for auditing. , which allows us to monitor the expectations gap for the external audit in Algeria and analyze its components The study was conducted based on two complementary methods, the first is documentary (descriptive) by looking at a number of literature to clarify the theoretical background of fiscal incentives and agricultural investment, and the second method is survey (analytical) through an exploratory study through the questionnaire as a tool for data collection, since the validity coefficient was measured as it was Reaching a high degree of reliability for a sample of (40) individuals. The data was analyzed using the statistical package (SPSS.V22) and descriptive statistical tools directed at accounting experts, account keepers "
ماستر محاسبة
Keywords: فجوة التوقعات، المراجعة الخارجية للحسابات، مسؤوليات المراجع، مهام المراجع; expectations gap, external audit, auditor responsibilities, auditor tasks.